2011
DOI: 10.1158/0008-5472.can-10-2987
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mathematical Modeling of IL13-Induced Signaling in Hodgkin and Primary Mediastinal B-Cell Lymphoma Allows Prediction of Therapeutic Targets

Abstract: Primary mediastinal B-cell lymphoma (PMBL) and classical Hodgkin lymphoma (cHL) share a frequent constitutive activation of JAK (Janus kinase)/STAT signaling pathway. Because of complex, nonlinear relations within the pathway, key dynamic properties remained to be identified to predict possible strategies for intervention. We report the development of dynamic pathway models based on quantitative data collected on signaling components of JAK/STAT pathway in two lymphoma-derived cell lines, MedB-1 and L1236, rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 44 publications
1
50
0
Order By: Relevance
“…In PMBCL, gene expression profiling revealed high levels of IL13 receptor expression and downstream effectors, such as JAK2 and STAT1, indicating up-regulation of pathway genes. 3,41,58 Moreover, constitutive STAT6 activation has been identified as a characteristic feature of PMBCL compared with DLBCL and, in contrast to cHL, this is probably not the result of autocrine IL-4 or IL-13 production. 8,59 Genomic amplification of a subtelomeric region of chromosome 9 (9p24.1) involving several genes, including JAK2, has been consistently reported in more than half of cases and can be considered as one of the hallmark genetic alterations in PMBCL 10,46,60,61 (Table 1).…”
Section: Jak-stat Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…In PMBCL, gene expression profiling revealed high levels of IL13 receptor expression and downstream effectors, such as JAK2 and STAT1, indicating up-regulation of pathway genes. 3,41,58 Moreover, constitutive STAT6 activation has been identified as a characteristic feature of PMBCL compared with DLBCL and, in contrast to cHL, this is probably not the result of autocrine IL-4 or IL-13 production. 8,59 Genomic amplification of a subtelomeric region of chromosome 9 (9p24.1) involving several genes, including JAK2, has been consistently reported in more than half of cases and can be considered as one of the hallmark genetic alterations in PMBCL 10,46,60,61 (Table 1).…”
Section: Jak-stat Signalingmentioning
confidence: 99%
“…As treatment recommendations are historically linked to DLBCL, the relative specificity of JAK-STAT, 8 NF-B pathway activation, 9 overexpression of PD-1 ligands, 3 and the histone-modifying genes JAK2 and JMJD2C 61 stand out as the most rational targets for specifically tailored future therapies in PMBCL. In vitro studies in MedB-1 cells demonstrate proof of principle that JAK pathway inhibition and reduction of STAT5 phosphorylation are toxic to the cells, 58 raising hope that similar approaches of JAK-STAT pathway inhibition might be a promising approach. Similarly, NF-B pathway inhibition has yielded promising results in preclinical models.…”
Section: Novel Therapeutic Approachesmentioning
confidence: 99%
“…Furthermore, STAT6 is a critical regulator in IL-4-mediated B-cell differentiation. Previous work has shown that B cells from mice lacking STAT6 failed to produce significant amounts of IgE and IgG1 after infection with the nematode parasites (Raia et al, 2011;Turqueti-Neves et al, 2014). The binding sites of STAT6 have been found in the target regions of a variety of IL-4-mediated genes, including CD23 (Cooper et al, 2012), IL-4R (Jenkins et al, 2013), eotaxin-1 (Waddell et al, 2013), eotaxin-3 (Nakayama et al, 2010), FIZZ1 (Dasgupta et al, 2011), and in Ig germline e (Lu et al, 2007) promoters.…”
Section: Introductionmentioning
confidence: 99%
“…Raia et al [2] used such expression data from cell lines of HL and primary mediastinal diffuse large B cell lymphoma (PMDLBL), tumor types with quite some similarities, including the constitutive activation of the JAK/STAT signaling pathway. They compare the data with those from normal B cells and find an increased level of STAT5 and 6.…”
Section: Biology Of Lymphomamentioning
confidence: 99%